2021
DOI: 10.3897/mycokeys.83.68926
|View full text |Cite
|
Sign up to set email alerts
|

New contributions to Diatrypaceae from karst areas in China

Abstract: In this study, fungal specimens of the family Diatrypaceae were collected from karst areas in Guizhou, Hainan and Yunnan Provinces, China. Morpho-molecular analyses confirmed that these new collections comprise a new genus Pseudodiatrype, three new species (Diatrype lancangensis, Diatrypella pseudooregonensis and Eutypa cerasi), a new combination (Diatrypella oregonensis), two new records (Allodiatrype thailandica and Diatrypella vulgaris) from China and two other known species (Neoeutypella baoshanensis and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Long & Q.R. Li were introduced by Dissanayake et al (2021) and Long et al (2021) , respectively, based on morphological distinctions and polygenic phylogenetic analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long & Q.R. Li were introduced by Dissanayake et al (2021) and Long et al (2021) , respectively, based on morphological distinctions and polygenic phylogenetic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Diatrype , Eutypa, and Eutypella are all unresolved lineages, and phylogenetic studies indicated that the three genera do not form monophyletic groups, even though they clustered within Diatrypaceae ( Hyde et al, 2020 ; Wijayawardene et al, 2020 ; Long et al, 2021 ; Yang et al, 2022 ). In an investigation of the diversity of wood-decaying fungi in southeastern Tibet of China, three undescribed species of diatrypaceous fungi were collected.…”
Section: Introductionmentioning
confidence: 99%
“…The comparisons of ITS and tub 2 sequences in NCBI both showed 100% (ITS = 530/530; 0 gaps; tub 2 = 358/358; 0 gaps) similarity to the strain of D. vulgaris (HVGRF03) from holotype specimens. D. vulgaris has been reported in Australia, Thailand, and China ( Trouillas et al, 2011 ; Hyde et al, 2017 ; Long et al, 2021 ). In this study, we introduce D. vulgaris as a new record from Sichuan province in China, and this is the first report on the genus Juglans .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we described 10 species in Dothideomycetes and Sordariomycetes associated walnut trees. Within the broader region of China, there are reports of partial fungi on other known or undescribed plants ( Zhang, 2003 ; Zhu et al, 2016 ; Jayawardena et al, 2018 ; Long et al, 2021 ; Farr and Rossman, 2022 ; Wanasinghe et al, 2022 ; Xu et al, 2022 ; Yang et al, 2022 ). To our knowledge, these are the first accounts of these species in Sichuan province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation